DEVELOPING CRITICAL THINKING SKILLS IN ACCOUNTING EDUCATION STUDENTS THROUGH THE CASE METHOD LEARNING APPROACH - Siti Fatimah; Ahmad Nurkhin; Rediana Setiyani; Jarot Tri Bowo Santoso (EDUCATIONE, 2026)
In the digital era and the rapid diffusion of artificial intelligence, universities are expected to produce graduates who can analyze information rigorously and make defensible judgments; however, critical thinking is often underdeveloped in accounting learning that remains content- and procedure-centered. This study aimed to evaluate the effectiveness of the Case Method Learning approach in strengthening the critical thinking skills of Accounting Education students in a Financial Accounting course. Using a quasi-experimental nonequivalent control group design, one experimental class received three cycles of case-based instruction, while a control class received conventional lecture-based instruction. Students’ critical thinking was measured with an accounting-specific instrument aligned with higher-order cognitive skills, administered through equivalent pretest–posttest tasks. Data were analyzed using paired-sample t-tests (within-group improvement) and independent-sample t-tests (between-group differences) in SPSS. Results showed a substantial gain in the experimental class, where the mean score increased from 5.97 (pretest) to 16.87 (posttest) with p = 0.000 (< 0.05), and post-intervention performance differed significantly from the control class (p = 0.000 (< 0.05)). These findings indicate that the case method can meaningfully enhance students’ analytical reasoning and problem-solving in accounting contexts. The study concludes that integrating structured cases into Financial Accounting instruction is an effective strategy for developing critical thinking among Accounting Education students. Practically, the results support curriculum-level adoption of case-based learning and lecturer capacity-building for designing authentic cases and facilitative discussions. Future research should test long-term retention, replicate across institutions and accounting topics, and combine quantitative outcomes with qualitative evidence on reasoning processes and classroom interaction.